2001
DOI: 10.1007/bf02235483
|View full text |Cite
|
Sign up to set email alerts
|

Storage time of transfused blood and disease recurrence after colorectal cancer surgery

Abstract: Transfusion of buffy-coat-depleted red cells suspended in saline, adenine, glucose, and mannitol blood stored for < 21 days may be an independent risk factor for development of recurrence after elective colorectal cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 32 publications
7
90
2
Order By: Relevance
“…However, Edna and Bjerkeset [6] failed to find any relationship between the time of blood storage and long-term prognosis. On the other hand, Mynster et al [20] showed that buffy-coat-depleted red cells stored for less than 21 day could be an independent risk factor for cancer recurrence, while blood stored more than 21 days had insignificant effect on the risk of recurrence. However, the results of these studies are difficult to compare because of the significant differences in their methodology.…”
Section: Discussionmentioning
confidence: 99%
“…However, Edna and Bjerkeset [6] failed to find any relationship between the time of blood storage and long-term prognosis. On the other hand, Mynster et al [20] showed that buffy-coat-depleted red cells stored for less than 21 day could be an independent risk factor for cancer recurrence, while blood stored more than 21 days had insignificant effect on the risk of recurrence. However, the results of these studies are difficult to compare because of the significant differences in their methodology.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Finally, the storage medium could be deleterious by generating superoxides and inflammatory mediators that could result in oxidative damage. [10][11][12][13] Observational studies, [14][15][16][17][18][19][20] although potentially confounded, 21,22 have suggested that these complicated mechanisms, often collectively referred to as "storage lesion," may adversely affect patient-important outcomes including infection, organ failure, hospital stay, and death. [14][15][16][17][18][19][20] Prior evidence on the age of transfused RBCs has been dominated by uncontrolled observational studies that suggest better outcomes with fresher RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different subgroups of infection, only wound infections were more frequent in patients receiving RBCs more than 21 days old 28 The clinical relevance of this change was studied in different patient populations. 6,10,[12][13][14][15][29][30][31] Recently, the effects of RBC storage duration have been evaluated in patients undergoing cardiac surgery and the rate of postoperative infections ranged from 4% to 15%. 10,12,29 In one study, Koch and colleagues 10 found that in patients receiving RBC transfusions during cardiac surgery, those treated with fresh blood (stored for 14 days) had a reduced occurrence of sepsis (2.8% vs. 4.0%, p 5 0.01) and renal failure (1.6% vs. 2.7%, p 5 0.003) than those receiving old blood, although differences in the baseline characteristics between the two groups could affect the ability to interpret the results.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…30 Nevertheless, the same authors showed in a second study that infection rates were similar in patients transfused with old blood (stored > 21 days) and fresh blood (stored for < 21 days; 34% vs. 29%). 31 However, the influence of old blood transfusion on outcomes of patients undergoing …”
mentioning
confidence: 99%